Reimagining the Law of the Sea: Evolution or Revolution? - Mossop, Joanna (Victoria University of Wellington Law Review, 2024)
This article explores the challenges for the United Nations Convention on the Law of the Sea (UNCLOS) in protecting the marine environment and biodiversity. The traditional approach to developing the law when facing new challenges is through evolution – the iterative amendment of existing instruments and guidelines. I discuss the recent Agreement for the Conservation and Sustainable Use of Marine Biodiversity in Areas beyond National Jurisdiction (BBNJ Agreement) as an example of the evolution approach. I challenge whether evolution in the law of the sea is sufficient to meet the significant challenges facing regulation of uses of the ocean, and ask whether revolution is needed, through new concepts and processes.